2017
DOI: 10.5897/ijps2017.4668
|View full text |Cite
|
Sign up to set email alerts
|

Spectral depth analysis for determining the depth to basement of magnetic source rocks over Nkalagu and Igumale areas of the Lower Benue Trough, Nigeria

Abstract: Structural interpretation of aeromagnetic data over Nkalagu-Igumale area of the Lower Benue Trough of Nigeria was carried out to determine the depth to magnetic basement and delineate the basement morphology and the structural features associated with the basin and their trends. The aeromagnetic data were subjected to series of computer based image and data enhancement techniques before spectral analysis. Results of the 2-D spectral analysis revealed two depths source models with the depth model (D1) for deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Structural trends within the study area as shown in the residual map are mainly NE-SW and NW-SE directions are in agreement with the fault orientation within the Benue Trough, with the NE-SW trends being dominant. The result from this study is in agreement with most of the depth estimation studies within the study area [1,14,[23][24][25][30][31]. The results obtained from spectral analysis for the depth to magnetic sources vary between 2.585 km to 4.878 km for deep structures, with a mean value of 3.415km and 0.135 km to 0.200 km for the shallow structures, with a mean value of 0.158 km.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Structural trends within the study area as shown in the residual map are mainly NE-SW and NW-SE directions are in agreement with the fault orientation within the Benue Trough, with the NE-SW trends being dominant. The result from this study is in agreement with most of the depth estimation studies within the study area [1,14,[23][24][25][30][31]. The results obtained from spectral analysis for the depth to magnetic sources vary between 2.585 km to 4.878 km for deep structures, with a mean value of 3.415km and 0.135 km to 0.200 km for the shallow structures, with a mean value of 0.158 km.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that magnetic intrusive bodies are present within the sediments. Ikeh et al [14] determined the depth to the basement of magnetic source rocks over Nkalagu and Igumale areas and calculated depth values of 2.15-5.25 km for the deep depth and 0.35-0.99 km for the shallow magnetic source bodies. Onwuemesi [28] using spectral analysis determined the sedimentary thickness of the Anambra basin to vary from 0.9km and 5.6km.…”
Section: Discussionmentioning
confidence: 99%
“…It is an elongated rifted depression that trends NE -SW direction and resting uncomfortably upon the Precambrian basement from the South where it merges with the Niger Delta to the North where its sediments are part of the Chad Basin succession. The Benue trough has generally three subdivisions namely; upper Benue trough, middle Benue trough and lower Benue trough (5) . The lower Benue trough which is underlain by a thick sedimentary sequence was formed as a result of series of tectonics and repetitive sedimentation in the cretaceous time (9,10) .…”
Section: Location and Geology Setting Of The Study Areamentioning
confidence: 99%
“…Developing and developed countries of the world have used geothermal energy in the generation of electricity to meet rapid increase in the demand for electricity to power households and industries. Geothermal energy is not widely known in Nigeria, although several authors (3)(4)(5)(6)(7)(8) etc., have carried out research on subsurface temperature across Nigeria. Therefore, delineating specific locations of underground thermal storage structure across Nigeria is important for geothermal energy generation and management.…”
Section: Introductionmentioning
confidence: 99%